Anxiety, Depression and Cancer‐Related Post‐Traumatic Stress in Patients Undergoing Total Laryngectomy - Mai Yokoi; Naoki Nishio; Hiroyuki Kimura; Tatsuya Tokura; Shinichi Kishi; Hidenori Tsuzuki; Nobuaki Mukoyama; Sayaka Yokoi; Akihisa Wada; Mayu Shigeyama; Yasushi Fujimoto; Masashi Ikeda; et al. (Laryngoscope Investigative Otolaryngology)
ABSTRACT Purpose This study aims to elucidate the incidence of cancer‐related post‐traumatic stress (PTS) and the fluctuations in anxiety and depression levels before and one year after laryngectomy. Methods A prospective longitudinal study was conducted on 97 consecutive patients scheduled to undergo laryngectomy (total laryngectomy or pharyngolaryngectomy) at a single university hospital between 2007 and 2022. To assess cancer‐related PTS, anxiety, and depression, participants completed two brief self‐reported questionnaires: the Impact of Event Scale‐Revised (IES‐R) and the Hospital Anxiety and Depression Scale (HADS). Results Prior to laryngectomy, 32 patients planning for the procedure were considered as cancer‐related PTS based on IES‐R. The prevalence of anxiety and depression before surgery was 56% and 76% in the 32 patients with PTS, respectively, compared to 8% and 20% in the 65 patients without PTS. Patients with PTS exhibited significantly worse HADS‐anxiety and HADS‐depression scores compared to those without PTS at baseline (p < 0.001 for both). Although no significant difference was found in the HADS‐anxiety score between the two groups (p = 0.15), patients with PTS exhibited a significantly worse HADS‐depression score than those without PTS one year after surgery (p = 0.03). Conclusion Early identification of possible depressive disorders and active psychiatric interventions are crucial for patients undergoing laryngectomy during the follow‐up period. Preoperative assessment of cancer‐related PTS may offer an opportunity to implement appropriate psychological interventions. Level of Evidence 4.